Notching a New Pathway in Vascular Flow Sensing. Issue 3 (March 2018) - Lagendijk, Anne K.; Yap, Alpha S.; Hogan, Benjamin M.
Abstract : Vascular barrier function is controlled at cell–cell junctions in response to blood flow, but how vascular endothelial cells sense and respond to flow remains to be understood. A recent study describes a flow-sensing pathway involving non-canonical Notch and cadherin signaling that sheds new light on mechanisms controlling the endothelial barrier.